On the taxonomy of Afrotropical Coleophoridae (VI). New species of the genus Coleophora Hübner, 1822 from South Africa (Lepidoptera, Coleophoridae) - Baldizzone, Giorgio (Zootaxa, 2021)
This work presents the description of 16 new species of the genus Coleophora Hübner from the Republic of South Africa: Coleophora animula sp. nov., C. parvula sp. nov., C. coniella sp. nov., C. afrobrunnea sp. nov., C. rocherpanensis sp. nov., C. comparata sp. nov., C. richtersveldi sp. nov., C. incomparabilis sp. nov., C. dixella sp. nov., C. cederbergensis sp. nov., C. curviphallica sp. nov., C. notabilis sp. nov., C. quaggaefontis sp. nov., C. tabulensis sp. nov., C. intricata sp. nov., C. transvaalensis sp. nov. A checklist of the 71 species currently known for South Africa is provided.